Estimation of ground motion during underground excavation - Muhammad Taufiq Rahmat (Nanyang Technological University, 2020)
Underground excavation in rock engineering has been a heated topic, due to its responsibility to the increase of seismicity and economic effect. Some uses of underground excavation include the construction of tunnels and caverns. There are various methods of underground excavation, which depends on the type of ground conditions and soil properties. One of these approaches is the Borehole-blasting method, which is commonly used in the construction of underground tunnels in Singapore as it speeds up the process. However, blasting results in seismic waves, which influences the building structure on the Earth’s surface. This usually results in the settlement of affected buildings, causing damages and cracks. The purpose of this project is to study the underground excavation-induced ground motion. Pre-existing fracture is simulated by the saw cut polycarbonate and the exploding mechanics is applied on the release of energy in the excavation. Normal stress acting on the polycarbonate sample is varied so that we can determine the relationship of normal stress with the rupture speed and ground motion. In the exploding-induced rupture experiments, the rupture speed is monitored by an array of strain gauges along the fracture, and the ground motion is measured by both of the Linear Variable Displacement Transformer (LVDT) and strain gauges on the simulated Earth’s surface. In the exploding-induced rupture experiments, under 3 MPa and 6 MPa normal stresses, we found that the rupture speeds are 902 m/s and 726 m/s, respectively, both of which are slower than S wave (960 m/s). Therefore, they are the sub-Rayleigh rupture. As the rupture speeds are in the same order but slightly different, more testing and improvement in the setup needs to be done to further improve the accuracy of the results. Moreover, we found that under 3 MPa and 6 MPa normal stresses and the same stress ratio (shear stress/normal stress) of 0.95, we obtained shear displacements of 0.0287 mm and 0.0319 mm, respectively. This shows that shear displacement increases with the increase in normal stress under the same stress ratio and hence concluded that there is a direct correlation between normal stress, shear stress and shear displacement.